LEXICAL GAPS IN O‘TKIR HOSHIMOV’S “BETWEEN TWO DOORS” AND THEIR CHALLENGES FOR NON-NATIVE READERS - Madraximova Dilnoza G‘ulom qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article explores lexical gaps in O‘tkir Hoshimov’s novel “Between Two Doors”. It analyzes how culturally specific terms, Soviet-era vocabulary, idiomatic expressions, and kinship terms create difficulties for non-native readers. The study shows that these gaps arise due to cultural and linguistic differences, as many Uzbek concepts do not have direct equivalents in other languages. The article also suggests practical strategies such as descriptive translation, cultural equivalence, and the use of annotations and glossaries to overcome these challenges. Overall, the research highlights the importance of preserving cultural meaning while making the text accessible to a wider audience.